Dėl Latgalės „giliųjų šnektų“ daugiskaitos kilmininko su -ūs kilmės - Rosinas, Albertas (Baltistica, 1997)
ON THE ORIGIN OF THE GENITIVE PLURAL -ūs IN LATGALE ‘DEEP’ SUBDIALECTS The problem of the origin of the genitive plural -ūs in Latgale ‘deep’ subdialects had already been investigated by J. Endzelīns, V. Mažiulis and A. Rosinas. Recently, the origin of the said ending has been attempted to establish by A. Breidaks as well. In his opinion, the genitive plural ending of pronominal adjectives and such anaphoric pronouns as tas, šis, jis, viņš is a phonetically modified relic of the Proto-Indo-European genitive dual *-ōs, i.e. Ide. *-ōs > East Balt. *-ōs > Latv. -u˚ > -ūs. The reconstruction of the Indo-European dual ending itself is hardly plausible, either (cf. Szemerényi et al.). V. Mažiulis, who has investigated the problem, came to the conclusion that the Indo-Europeans had never possessed such a dual ending. He maintains that in Proto-Baltic the o-stem genitive-‘locative’ form was *-au (Ide. *-ou) which acquired the formant -s from the hypothetical locative plural *(t)uos < *(t)-ōs not in the period of Proto-Baltic but much later, i.e. when, due to apophonic reasons, the genitive-‘locative’ dual *(t)-au changed into *(t)-uo. The hypothesis advanced by V. Mažiulis is reliable in two respects: a) that the Balts did not possess the genitive dual *(t)-ōs and b) that (t)-ūs in Latgale subdialects is a late innovation. However, the statement that the formant -s was added to -au on the analogy of the hypothetical locative form *(t)-uos still remains doubtful. Dealing with the problem, it is necessary to take into consideration the two processes of text composition, i.e. ‘focusing’ and ‘anaphorisation’. The unmarked elements of the information which possess the feature –Fm (i.e. not the first mention) never occur in the focus. Here belong pronominal adjectives and the aforesaid pronouns. Dual forms could have been preserved only in these words and phrases (i.e. numerals and quantative nominal phrases) which occur in the focus. In anaphoric structures, their old dual was replaced by the unmarked member plural of the opposition plural / dual. Therefore, the possibility of retaining the old dual forms in words used anaphorically was zero. The hypothetical dual ending could, however, been retained only by nouns and the numeral divi which has the meaning of duality. In Latgale and Sēlija subdialects the said numeral and nouns have the ending -u, and not -ūs. The hypothesis advanced by A. Breidaks has stimulated the thought presented here and confirmed my hypothesis of 1971 which claims that the genitive plural ending -us in Latgale subdialect is a relatively recent innovation which formed after morphonological and prosodic changes in word-final position which were followed by the syncretism of the cases.